2016
DOI: 10.1111/bjd.14656
|View full text |Cite
|
Sign up to set email alerts
|

The evolving regulatory role of ubiquitin-editing enzyme A20 in psoriasis during calcipotriol treatment

Abstract: Linked Article: Liu et al. Br J Dermatol 2016; 175:314–324.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…[49] showed that TNFAIP3 protein is over-expressed under psoriatic inflammation, favoring keratinocyte proliferation and suppressing apoptosis. This strong expression of TNFAIP3 found in lesional psoriatic skin has been posited to inhibit the NF-κB pathway; however, a strong expression of NF-κB was observed [49], suggesting that TNFAIP3 is disabled or dysfunctional in patients with psoriasis [50]. It is worth mentioning that in psoriatic patients with higher TNFAIP3 expression levels in their skin lesions compared to normal controls, calcipotriol (a vitamin D3 analogue) therapy significantly reduced the expression levels of both TNFAIP3 and NF-κB [49, 51].…”
Section: Discussionmentioning
confidence: 99%
“…[49] showed that TNFAIP3 protein is over-expressed under psoriatic inflammation, favoring keratinocyte proliferation and suppressing apoptosis. This strong expression of TNFAIP3 found in lesional psoriatic skin has been posited to inhibit the NF-κB pathway; however, a strong expression of NF-κB was observed [49], suggesting that TNFAIP3 is disabled or dysfunctional in patients with psoriasis [50]. It is worth mentioning that in psoriatic patients with higher TNFAIP3 expression levels in their skin lesions compared to normal controls, calcipotriol (a vitamin D3 analogue) therapy significantly reduced the expression levels of both TNFAIP3 and NF-κB [49, 51].…”
Section: Discussionmentioning
confidence: 99%